Preparation method of SA / CS / Ca2 + dual-network hydrogel, obtained product and application of SA / CS / Ca2 + dual-network hydrogel

Through the preparation method of SA/CS/Ca2+ dual network hydrogel, sodium alginate, chitosan and calcium ions are used to form a physically cross-linked dual network structure, which solves the problem of insufficient mechanical properties of the existing hydrogel, and achieves high hardness, stability and low toxicity hydrogel preparation.

CN119639028AActive Publication Date: 2025-03-18SHANDONG ACADEMY OF AGRICULTURAL SCIENCES

Patent Information

Application Number
CN202411850302.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Existing hydrogels have shortcomings in mechanical properties, are soft and fragile, and most dual network hydrogels require chemical crosslinking agents, which has toxicity problems.

Method used

The preparation method of SA/CS/Ca2+ dual network hydrogel is adopted to form a physically cross-linked dual network structure through the interaction of sodium alginate, chitosan and calcium ions, and combined with semi-dissolved acidified sol-gel transformation method and internal gel method to improve the hardness and stability of the gel.

Benefits of technology

It significantly improves the hardness, chewability and elasticity of the hydrogel, improves the cohesion and structural stability of the gel, avoids the use of chemical crosslinking agents, and reduces the risk of toxicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639028A_ABST
    Figure CN119639028A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of hydrogel preparation, and particularly relates to a preparation method of SA / CS / Ca < 2 + > dual-network hydrogel, an obtained product and application. The sodium alginate / chitosan / calcium ion (SA / CS / Ca < 2 + >) physical cross-linked double-network hydrogel is prepared through a semi-dissolution acidification sol-gel conversion method and an internal gel method, the hardness and chewiness of the hydrogel can be remarkably improved, and the elasticity and cohesiveness of the hydrogel can be improved; freeze-thaw stability research is carried out on the prepared SA / CS / Ca < 2 + > dual-network hydrogel, the influence of freezing temperature, thawing temperature, freezing and thawing cycle times and other conditions on properties such as gel structure, rheology, swelling rate, moisture distribution and the like is explored, and the result shows that when the freezing temperature is-80 DEG C and the thawing temperature is 4 DEG C, the gel subjected to one-time freezing and thawing cycle has good stability. Through detection and analysis, the hardness is relatively high, the elasticity and cohesiveness are also remarkably improved, the elastic modulus (G ') and the viscous modulus (G' ') of the gel are best, the swelling rate is relatively low, the free water content is relatively low, the bound water content is relatively high, and the gel structure is relatively stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of hydrogel preparation, and specifically relates to a SA / CS / Ca 2+ The invention discloses a preparation method of double network hydrogel and the obtained products and applications. Background Art

[0002] Hydrogel is a three-dimensional network structure formed by cross-linking, entanglement and folding of molecular chains. Due to its strong hydrophilicity, high water content, large porosity, and artificially adjustable physical and chemical properties, hydrogels are widely used in industry, environment, biomedicine and other fields. At present, sodium alginate (SA) and chitosan (CS) are widely used in the production of functional hydrogels, but the problem faced by most hydrogels is that they are soft and fragile and have weak structures. In order to improve their mechanical properties, double network hydrogels (DH) are used to improve the mechanical properties of the gel and make the gel structure more stable. DH is a hydrogel composed of two interpenetrating or semi-interpenetrating polymer networks with different physical and chemical properties. The first network is tightly bound to enhance the strength of the hydrogel, and the second network has a low degree of crosslinking, which improves the flexibility and toughness of the hydrogel. However, most double network hydrogels have added chemical crosslinkers with greater toxicity, so it is necessary to prepare and develop physically crosslinked double network hydrogels.

[0003] SA is an anionic polyelectrolyte with a large number of negatively charged carboxyl groups on its molecular chain, while CS is a cationic electrolyte with a large number of positively charged amino groups on its molecular chain.

[82] SA and CS can form a SA / CS network structure through electrostatic interaction. At the same time, the guluronic acid block in the SA structure can interact with Ca 2+ Chelation to form SA / Ca 2+ However, this structure does not have sufficient mechanical properties, so how to improve the mechanical properties of hydrogels has become an urgent problem to be solved. And because the electrostatic interaction occurs quickly, CS and SA react easily to produce large irregular gels, and when SA solution is directly added to Ca 2+ When the gel is in solution, it will produce gel microspheres. The surface of the gel spheres first contacts the Ca 2+ solution to cross-link, hindering the Ca 2+ Penetrate further inward. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a SA / CS / Ca 2+ Preparation method of double network hydrogel.

[0005] Another object of the present invention is to provide a SA / CS / Ca prepared by the above preparation method. 2+ Double network hydrogel.

[0006] The present invention also provides SA / CS / Ca 2+ Applications of double network hydrogels.

[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: The present invention provides a SA / CS / Ca 2+ The preparation method of the double network hydrogel comprises the following steps: (1) Weigh sodium alginate, add it into distilled water, and stir to obtain a sodium alginate solution; (2) Weigh a certain amount of calcium carbonate powder, add it to the sodium alginate solution, and continue stirring using a constant temperature magnetic stirrer after ultrasonic treatment to obtain a sodium alginate-calcium carbonate mixture; (3) Weigh a certain amount of chitosan powder, add it to the sodium alginate-calcium carbonate mixture, and stir overnight after ultrasonication; (4) Weigh a certain amount of gluconolactone (GDL) powder, add it to the mixed solution, quickly stir it evenly, and then let it stand to form a hydrogel; (5) The hydrogel is subjected to freeze-thaw treatment.

[0008] Furthermore, in step (1), the mass concentration of the sodium alginate solution is 0.01-0.03 g / mL.

[0009] Furthermore, in step (2), the mass ratio of calcium carbonate to sodium alginate is 0.1-0.5:1-3; the ultrasonication time is 30 min; and the stirring time is 2 h.

[0010] Furthermore, in step (3), the mass ratio of the chitosan powder to the sodium alginate is 1-3:1-3; the ultrasonic time is 60 minutes; Furthermore, in step (4), the mass ratio of gluconolactone to chitosan is 0.25:1-3.

[0011] Furthermore, in step (5), the freeze-thaw treatment is to place the hydrogel in a -80°C refrigerator for 24 h and then thaw it at 4°C for 24 h. The present invention also provides a SA / CS / Ca2+ double network hydrogel prepared by the above preparation method.

[0012] The present invention further provides the SA / CS / Ca 2+ Application of double network hydrogel in preparing composite materials by embedding MCT.

[0013] The beneficial effects of the present invention are: (1) The present invention prepares sodium alginate / chitosan / calcium ion (SA / CS / Ca) by semi-dissolving acidified sol-gel transition method and internal gel method. 2+ ) Physically cross-linked double network hydrogel can significantly improve the hardness and chewiness of the hydrogel, and improve the elasticity and cohesion of the hydrogel; (2) The present invention prepares SA / CS / Ca 2+ The freeze-thaw stability of double network hydrogel was studied to explore the effects of freezing temperature, melting temperature, freeze-thaw cycle number and other conditions on gel texture, rheology, swelling rate, water distribution and other properties. The results showed that when the freezing temperature was -80°C and the melting temperature was 4°C, the gel after one freeze-thaw cycle had a higher hardness, and its elasticity and cohesion were significantly improved. The gel elastic modulus (G′) and viscosity modulus (G″) were the best, the swelling rate was small, and the water distribution showed less free water and more bound water, and the gel structure was more stable. (3) SA / CS / Ca prepared by the present invention 2+ Double network hydrogel, medium chain triglyceride (MCT) was embedded, and the embedding rate was used as an indicator. It was determined that when the emulsified MCT was added to the solution before the gel was formed, the embedding rate reached a maximum of 94.62%; the embedded gel was porous and stable by scanning electron microscopy; the final gel formed by Fourier infrared spectroscopy showed characteristic peaks of CS, SA and MCT, and the gel formation process did not involve the formation of chemical bonds. The in vitro simulated digestion test showed that the release rate of MCT hydrogel after embedding was slow, the digestion effect was good, and SA / CS / Ca 2+ Double-network hydrogel-embedded MCT has a sustained-release effect, and the release kinetics analysis is consistent with the first-order kinetic model, which can enable MCT to play a greater role and enhance the stability of MCT. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The frequency scanning results of different SA concentrations of the hydrogel prepared in Example 1; Figure 2 The frequency scanning results of different CS concentrations of the hydrogel prepared in Example 1; Figure 3 The hydrogel prepared in Example 1 has different Ca 2+ Concentration frequency scanning knot; Figure 4 The swelling rate results of the hydrogels prepared in Example 1 at different SA concentrations; Figure 5 The swelling rate results of the hydrogel prepared in Example 1 at different CS concentrations; Figure 6 The hydrogel prepared in Example 1 has different Ca 2+Concentration swelling ratio results; Figure 7 The three-dimensional response surface map and contour map of the hydrogel prepared in Example 1; Figure 8 Results of the effect of freezing temperature on the rheological properties of gel (A) apparent viscosity, (B) strain sweep, (C) frequency sweep, (D) recovery effect; Fig. 9 Effect of melting temperature on the rheological properties of gel (A) apparent viscosity, (B) strain sweep, (C) frequency sweep, (D) recovery effect; Fig.10 Results of the effect of freeze-thaw cycles on the rheological properties of gels (A) apparent viscosity, (B) strain sweep, (C) frequency sweep, and (D) recovery effect; Fig.11 The results of freeze-thaw effects on gel swelling rate; Fig.12 Comparison of embedding rates among four groups of samples; Fig.13 Scanning electron micrographs of the sample group (a: non-emulsified MCT embedded after gelation, b: emulsified MCT embedded before gelation, c: emulsified MCT embedded after gelation) and the blank group; Fig.14 Infrared spectra of gel (control group is gel without MCT embedding); Fig.15 Comparison of release rates of MCT and gel-encapsulated MCT (SA1 is SA-encapsulated unemulsified MCT sample, SA2 is SA-encapsulated emulsified MCT emulsion); Fig.16 Comparison of release rates of embedded MCT gel after freezing and thawing and before freezing and thawing (D1 is the sample of sample 1 after freezing and thawing, D2 is the sample of sample 2 after freezing and thawing, D3 is the sample of sample 3 after freezing and thawing, and D4 is the sample of sample 4 after freezing and thawing). DETAILED DESCRIPTION

[0015] The technical solution of the present invention is further explained and illustrated by means of specific embodiments below.

[0016] Unless otherwise specified, the raw materials used in the present invention are commercially available.

[0017] The instruments and equipment used in the present invention are shown in Table 1.

[0018] Table 1 Example 1 1.0 g, 1.5 g, 2.0 g, 2.5 g, and 3.0 g of sodium alginate were added to 100 mL of distilled water and stirred for 2 h using a constant temperature magnetic stirrer to obtain a sodium alginate solution with a certain mass fraction; 0.1 g, 0.2 g, 0.3 g, 0.4 g, and 0.5 g of calcium carbonate powder were weighed and added to the prepared sodium alginate solution, ultrasonicated for 30 min, and then stirred for 2 h using a constant temperature magnetic stirrer; 1.0 g, 1.5 g, 2.0 g, 2.5 g, and 3.0 g of chitosan powder were weighed and added to the sodium alginate-calcium carbonate mixture, ultrasonicated for 60 min, and then stirred overnight; 0.25 g of gluconolactone (GDL) powder was weighed and added to the mixed solution, quickly stirred evenly, and then allowed to stand to form a hydrogel.

[0019] Effect Example 1 1. Response surface experiment Under the premise of single factor experiment, the significant factors and optimal conditions were determined, and the Design Expert 8.0 software was used to conduct response surface design and analysis on the three factors of sodium alginate addition, calcium carbonate addition and chitosan addition, taking the swelling rate as the evaluation index.

[0020] 2. Determination of gel texture characteristics The prepared gel was placed in a culture dish and tested at room temperature using the TPA mode and an aluminum cylindrical probe (P / 36R). The test conditions were as follows: the compression strain was set to 50%, the speed before, during, and after the test was 1 mm / s, the trigger force was 10 g, and the dwell time was 5 s. The hardness, elasticity, chewiness, and cohesion of the gel were measured, and the samples were measured three times in parallel.

[0021] 3. Determination of gel rheological properties At 25°C, a 40 mm parallel plate was used to perform frequency sweeps at a strain of 1% and an angular frequency range of 0.1-100 rad / s. The changes of storage modulus (G') and loss modulus (G") with frequency were recorded. The samples were measured three times in parallel.

[0022] (IV) Determination of gel swelling rate Take a hydrogel of appropriate size, freeze dry it with a freeze dryer, and weigh it, and record the mass as M0. Incubate it in deionized water at room temperature, take it out after 24 hours, wipe it clean, and weigh it, and record the mass as M1. The sample is measured three times in parallel.

[0023] (V) Data analysis and processing The present invention uses Origin 2021 software to draw charts, and IBM SPSS Statistics 27 software to perform data analysis. Each sample was repeated at least three times, and the experimental data were expressed as mean ± standard deviation.

[0024] (VI) Test results and analysis (1) Analysis of texture characteristics The texture characteristics of gel are often analyzed using the TPA mode of texture analyzer. According to the characteristics of gel, hardness, chewiness, springiness, and cohesiveness are selected as research parameters.

[0025] ① Effect of SA concentration on texture characteristics Table 2 Effect of SA concentration on gel texture properties Note: Different lowercase letters in the same column of data indicate significant differences (p<0.05) As shown in Table 2, in Ca 2+ When the concentration of CS is constant, as the concentration of SA increases, the number of carboxyl groups also increases, which improves the cross-linking strength and electrostatic interaction of the gel, making the formed gel stronger and harder. When the concentration of SA increases from 1% to 2.5%, the hardness of the gel increases significantly, the energy required for chewing to swallowing increases, and the chewing degree increases significantly; when the concentration of SA is 2.5%, the texture of the gel is the best.

[0026] ② Effect of CS concentration on texture characteristics Table 3 Effect of CS concentration on gel texture properties Note: Different lowercase letters in the same column of data indicate significant differences (p<0.05) As shown in Table 3, in SA and Ca 2+ When the concentration is constant, as the concentration of CS increases, the amino group (-NH3 + ) also increases, which strengthens the electrostatic interaction of the gel and makes the formed hydrogel stronger. Therefore, the hardness of the gel with a concentration of 1% to 2% CS increases significantly, and the energy required for chewing to swallowing increases, so the chewing degree increases significantly, and the elasticity and cohesion also increase. + When it increases to a certain extent, there may be a large number of amino groups that do not interact electrostatically with the carboxyl groups, and the remaining -NH3 +The electrostatic repulsion will cause the gel to swell, so when the CS concentration is 2.5%~3%, the gel hardness decreases, the chewiness also decreases, and the elasticity and cohesion also decrease slightly. Therefore, when the CS concentration is 2%, the texture characteristics of the gel are the best.

[0027] ③Ca 2+ Effect on texture properties Table 4 Different Ca 2+ Effect of concentration on gel texture properties Note: Different lowercase letters in the same column of data indicate significant differences (p<0.05) It can be seen from Table 4 that when Ca 2+ When the concentration increased from 0.1 mol / L to 0.3 mol / L, the hardness of the gel increased significantly from 523.72 g to 762.96 g. 2+ When the concentration increases from 0.4 mol / L to 0.5 mol / L, the excess Ca 2+ It will interfere with the synergistic interaction between polysaccharides, reduce the gelation ability, reduce the gel strength, and lead to a decrease in gel hardness and chewiness. 2+ When the concentration is 0.3 mol / L, the texture properties of the gel are the best.

[0028] (2) Analysis of rheological properties results ① Effect of SA concentration on rheological properties Depend on Figure 1 It can be seen that the elastic modulus (G′) and viscous modulus (G′′) increase with increasing frequency, and G′ at each concentration is greater than G″, indicating that the sample has elastic and gel-like behavior. When the SA concentration is from 1% to 2%, the elastic modulus (G′) and viscous modulus (G′′) of the gel increase significantly with increasing frequency. When the SA concentration is 2.5% to 3%, the elastic modulus (G′) and viscous modulus (G′′) of the gel decrease with increasing frequency. When the SA concentration is 2%, the viscoelasticity of the gel is the best.

[0029] ② Effect of CS concentration on rheological properties Depend on Figure 2It is known that the elastic modulus (G′) and viscous modulus (G′′) increase with increasing frequency, and G′ at each concentration is greater than G″, indicating that the sample has elastic and gel-like behavior. With the increase of chitosan content in the hydrogel, the elastic modulus (G′) and viscous modulus (G′′) of the hydrogel also gradually increase. When the chitosan concentration is from 1% to 1.5%, the elastic modulus (G′) and viscous modulus (G′′) of the gel increase. When the CS concentration is from 2% to 3%, the elastic modulus (G′) and viscous modulus (G′′) of the gel gradually decrease. When the CS concentration is 1.5%, the viscoelasticity of the gel is the best.

[0030] ③Ca 2+ Effect of concentration on rheological properties Depend on Figure 3 It can be seen that the elastic modulus (G′) and viscous modulus (G′′) increase with the increase of frequency, and G′ at each concentration is greater than G″, indicating that the sample has elastic and gel-like behavior. 2+ When the concentration ranges from 0.1 mol / L to 0.3 mol / L, the elastic modulus (G′) and viscous modulus (G′′) of the gel increase significantly with the increase of frequency. 2+ When the concentration is 0.4 mol / L~0.5 mol / L, the elastic modulus (G′) and viscous modulus (G′′) of the gel decrease with the increase of frequency; 2+ When the concentration is 0.3 mol / L, the viscoelasticity of the gel is the best.

[0031] (III) Analysis of swelling rate results ① Effect of SA concentration on swelling rate Depend on Figure 4 It can be seen that when the SA concentration ranges from 1% to 2%, the swelling rate of the gel decreases from 25.50% to 17.40%; when the SA concentration is 2.5~3%, the swelling rate increases from 18.64% to 19.69%; when the SA concentration is 2%, the swelling performance of the gel is the best.

[0032] ② Effect of CS concentration on swelling rate Depend on Figure 5 It can be seen that when the CS concentration is from 1% to 1.5%, the swelling rate of the gel decreases. When the CS concentration is from 2% to 3%, the swelling rate of the gel gradually increases; when the CS concentration is 1.5%, the swelling performance of the gel is the best.

[0033] ③Ca 2+ Effect of concentration on swelling rate Depend on Figure 6 It can be seen that when Ca 2+ When the concentration was 0.1 mol / L~0.3 mol / L, the swelling rate of the gel gradually decreased; 2+ When the concentration is 0.4 mol / L~0.5 mol / L, the swelling rate gradually increases. This may be due to the Ca 2+ The increase in concentration increases the number of grids between the molecular chains, making it easier for water molecules to penetrate inward, thereby increasing the swelling rate of the gel. 2+ When the concentration is 0.3 mol / L, the swelling performance of the gel is the best.

[0034] 4. Response surface analysis Based on the significant factors and optimal results of the single-factor test, the Box-Behnken method was used to analyze the SA, CS, and Ca 2+ A response surface experimental design was performed on the concentrations.

[0035] Table 5 Experimental factor level table Regression analysis was performed using Design-expert V8.0. The results are shown in Table 6.

[0036] Table 6 Box-Behnken test design and results Table 7 Analysis of variance table of response surface model The experimental data were statistically analyzed using Design-Expert 10.0.1 software, and the quadratic polynomial regression equation was obtained: Swelling rate = 96.17-0.67A+0.4B-0.097C+0.22AB-0.2AC-0.085BC-3.21A 2 -2.92B 2 -2.64C 2 The P value of the response surface model is 0.0001, indicating that the quadratic equation model is extremely significant. The coefficient of determination is R 2 =0.9827, indicating that the regression model has a good fit and the regression equation is representative. 98.27% of the change in the response value comes from the selected variables. The model adjustment coefficient is R 2 Adj =0.9604, indicating that the model has good predictive ability and the actual value is close to the predicted value; the model precision is 16.1522, which is greater than 4, indicating that the model is feasible.

[0037] In the response surface experiment, the influence of the three factors on the swelling rate can be determined by the F value. The higher the F value, the greater the influence of the factor on the swelling rate. According to the test results, the order of influence of the above factors on the swelling rate is SA (A) > CS (B) > Ca 2+ (C) The factor that has the greatest impact on the swelling rate is the concentration of SA.

[0038] The contour lines and response surfaces made by pairwise factors are Figure 7 It can be seen that the interaction effects between the above four factors have a trend of increasing first and then decreasing on the swelling rate. The shape of the contour map reflects the size of the interaction effect between the two factors. The closer the contour map is to an ellipse, the more significant the interaction between the factors is in affecting the swelling rate. Figure 7 It can be seen that SA and Ca 2+ Concentration interaction and SA / CS concentration interaction have a greater impact on the swelling rate.

[0039] According to the obtained model, the conditions were optimized using Design-Expert 8.0. The optimal conditions were as follows: SA concentration was 2.14%, CS concentration was 1.7%, Ca 2+ The concentration of 0.31 mol / L, under which condition the swelling rate can reach 17.20%. Under the optimal process conditions, verification tests were carried out, and repeated experiments showed that the swelling rate can reach 17.01%, close to the theoretical optimal value, with good repeatability, proving that the experimental results are reliable.

[0040] Example 2 (1) Add 2.14 g of sodium alginate into 100 mL of distilled water and stir for 2 h using a constant temperature magnetic stirrer to obtain a sodium alginate solution with a certain mass fraction. Secondly, weigh 0.31 g of calcium carbonate powder and add it to the prepared sodium alginate solution. After ultrasonic treatment for 30 min, continue stirring for 2 h using a constant temperature magnetic stirrer. Then weigh 1.7 g of chitosan powder and add it to the sodium alginate-calcium carbonate mixture. After ultrasonic treatment for 60 min, stir overnight. Finally, weigh 0.25 g of gluconolactone (GDL) powder and add it to the mixed solution. Stir quickly and evenly and let it stand to form a hydrogel.

[0041] (2) The freeze-thaw process was divided into three groups for experiment: Group 1: The gel was placed in a -20℃ and -80℃ refrigerator for 24 h, and then thawed at 4℃ for 24 h. Group 2: The gel was placed in a -80℃ refrigerator for 24 h, and then thawed at 4℃ and 25℃ for 24 h. Group 3: The gel was placed in a -80℃ refrigerator for 24 h, and then thawed at 25℃ for 24 h, and then a freeze-thaw cycle was performed again.

[0042] Effect Example 2 1. Analysis of texture characteristics (1) Effect of freezing temperature on gel texture properties Table 8 Effect of freezing temperature on gel texture properties As shown in Table 8, compared with the unfrozen gel, the texture characteristics of the frozen-thawed gel have been significantly improved. The gel prepared at a freezing temperature of -80°C has a higher hardness, and the internal structure of the gel is more compact and stable, which can provide better support. The higher the hardness of the gel, the more energy is required for chewing and swallowing, and the chewing degree is significantly increased.

[0043] In terms of elasticity and cohesion, the -80℃ gel also improved significantly compared with the -20℃ gel. 2+ The double network hydrogel has good texture properties.

[0044] (2) Effect of melting temperature on gel texture properties Table 9 Effect of melting temperature on gel texture properties As shown in Table 8, different melting temperatures have different effects on the texture properties of the gel. The hardness and chewiness of the gel at a melting temperature of 25°C are less than that of the gel at a melting temperature of 4°C. This may be because when the melting temperature is 25°C, the ice crystals begin to melt and the water refills the voids and pores inside the gel. Therefore, when the melting temperature is 4°C, the freeze-thaw SA / CS / Ca 2+ The double network hydrogel has good texture properties.

[0045] (3) Effect of freeze-thaw cycles on gel texture properties Table 10 Effect of freeze-thaw cycles on gel texture properties As shown in Table 10, the gel hardness and chewiness after the second freeze-thaw cycle were significantly lower than those after the first freeze-thaw cycle and the second freeze-thaw cycle. 2+ The double network hydrogel has good texture properties.

[0046] (II) Analysis of rheological properties results The hydrogel structure contains a large amount of water, and ice crystals will be produced during the freezing and thawing process, which will affect the original structure. Given that the freezing and thawing process has a great influence on the hydrogel, the effects of freezing temperature, melting temperature, and the number of freezing and thawing cycles on the hydrogel structure were investigated. 2+ Effect of rheological properties of gel.

[0047] (1) Effect of freezing temperature on gel rheological properties Figure 8 The relationship between the apparent viscosity (η) and shear rate of the gel after freezing at -20℃ and -80℃ is shown. It can be seen from the figure that the η value of the gel after freezing at -20℃ and -80℃ decreases with the increase of shear rate, showing a pseudoplastic fluid, which is consistent with the trend of the gel without freezing and thawing. As shown in the figure, the gel after freezing at -20℃ and -80℃ was strain scanned to determine the range of the linear viscoelastic region. In the strain range of 0.1%~1%, the viscoelasticity of the gel did not change with the change of strain scanning. Therefore, the strain value was selected as 1 Pa, and the gel after freezing and thawing was subjected to frequency scanning to study the effect of freezing temperature on the elastic modulus and viscous modulus of the gel. The figure shows the elastic modulus (G′) and viscous modulus (G″) as a function of frequency. With the increase of shear rate, G′>G′′, showing good gel properties, and the viscoelasticity of the gel after freezing and thawing is greater than that of the gel without freezing and thawing. The possible reason is that the interaction between molecular chains under freezing conditions makes the formed network structure more stable, and the G′ and G″ after freezing at -80℃ are greater than -20℃. Therefore, when the freezing temperature is -80℃, the SA / CS / Ca 2+ The rheological properties of the gel are good.

[0048] The modulus change of the gel after freezing at -20℃ and -80℃ was investigated by alternating scanning of 1% and 500%. In the three strain scans, the modulus of the mixture remained unchanged and G′>G′′, maintaining a semi-solid gel state, then G′ decreased and G′′ increased, G′<G′′ showed a liquid state, and finally recovered to a semi-solid gel state (G′>G′′), which was caused by different external forces on the system. However, after three scans, the G′ of the gel decreased, because the internal structure of the system was irreversibly damaged during the action of a large external force, resulting in energy loss, which led to a decrease in the strength of the system gel.

[0049] (2) Effect of melting temperature on gel rheological properties The freeze-thaw process has a significant impact on the rheological properties of the gel, among which the melting temperature is one of the key factors. When the gel undergoes a freezing and then melting process, the change in melting temperature will directly affect the rheological behavior of the gel. Fig. 9The relationship between the apparent viscosity (η) and shear rate of the gels that were frozen at -80℃ and then melted at 4℃ and 25℃ is shown. As can be seen from the figure, the η value of the gels melted at 4℃ and 25℃ decreases with the increase of shear rate, showing a pseudoplastic fluid, which is consistent with the trend of the gels that have not been frozen and thawed. As shown in the figure, the gels melted at 4℃ and 25℃ were strain scanned to determine the range of the linear viscoelastic region. In the strain range of 0.1%~1%, the viscoelasticity of the gel does not change with the change of the strain scan. Therefore, the strain value is selected as 1 Pa, and the gels after freeze-thaw are subjected to frequency scanning to study the effect of freezing temperature on the elastic modulus and viscous modulus of the gel. The figure shows the elastic modulus (G′) and viscous modulus (G″) as a function of frequency. With the increase of shear rate, G′>G″, showing good gel properties, and the viscoelasticity of the gel after freeze-thaw is greater than that before freeze-thaw. The possible reason is the migration of water during freeze-thaw and the formation of a denser network structure. The G′ and G″ of the gel melted at 4°C are both greater than 25°C, indicating that the lower melting temperature may cause the ice crystals in the gel to melt more slowly, the cross-linking structure inside the gel is relatively stable, the viscoelastic modulus is larger, and it shows higher rigidity and elasticity.

[0050] The modulus change of the gel after melting at 4°C and 25°C was investigated by alternating scanning of 1% and 500%. In the three strain scans, the modulus of the mixture remained unchanged and G′>G′′, maintaining a semi-solid gel state, then G′ decreased and G′′ increased, G′<G′′ showed a liquid state, and finally recovered to a semi-solid gel state (G′>G′′), which was caused by different external forces on the system. However, after three scans, the G′ of the gel decreased, because the internal structure of the system was irreversibly damaged during the action of a large external force, resulting in energy loss, which led to a decrease in the strength of the system gel.

[0051] (3) Effect of freeze-thaw cycles on gel rheological properties Fig.10 The relationship between the apparent viscosity (η) and shear rate of the gel after no freeze-thaw, one freeze-thaw cycle, and two freeze-thaw cycles is shown. As can be seen from the figure, the η value of the gel after one freeze-thaw cycle and two freeze-thaw cycles decreases with the increase of shear rate, showing a pseudoplastic fluid, which is consistent with the trend of the gel without freeze-thaw. As shown in the figure, the gel after one freeze-thaw cycle and two freeze-thaw cycles was strain scanned to determine the range of the linear viscoelastic region. In the strain range of 0.1%~1%, the viscoelasticity of the gel did not change with the change of the strain scan, so the strain value was selected as 1 Pa. The gel after one freeze-thaw cycle and two freeze-thaw cycles was frequency scanned to study the effect of the number of freeze-thaw cycles on the elastic modulus and viscous modulus of the gel. Fig.10The effect of the number of freeze-thaw cycles on the elastic modulus (G′) and viscous modulus (G″) of the gel is shown. With the increase of shear rate, G′>G″, showing good gel properties, while G′ and G″ after two freeze-thaw cycles are significantly smaller than G′ and G″ after one freeze-thaw cycle and without freeze-thaw. This is because when the cross-linking strength of the gel given by the freeze-thaw treatment exceeds a certain limit, freezing and thawing again will lead to excessive cross-linking and a decrease in gel strength. With the increase of the number of freeze-thaw cycles, the gel network becomes loose and broken, resulting in a decrease in the rheological viscoelastic modulus of the gel. Therefore, in one freeze-thaw cycle, the freeze-thaw SA / CS / Ca 2+ The rheological properties of the gel are good.

[0052] The modulus changes of the gel after one freeze-thaw cycle and two freeze-thaw cycles were investigated by alternating 1% and 500% scanning. In the three strain scans, the modulus of the mixture remained unchanged and G′>G′′, maintaining a semi-solid gel state, then G′ decreased and G′′ increased, G′<G′′ showed a liquid state, and finally recovered to a semi-solid gel state (G′>G′′), which was caused by different external forces on the system. However, after three scans, the G′ of the gel decreased.

[0053] (III) Analysis of swelling rate results Depend on Fig.11 It can be seen that the swelling rate of the gel at a freezing temperature of -80°C is less than that at -20°C. This may be because the freezing temperature of -20°C leads to the formation of larger ice crystals, which will form larger voids and pores inside the gel. Therefore, the pore structure of the gel is looser and the swelling rate increases accordingly. Therefore, at a freezing temperature of -80°C and a melting temperature of 4°C, the structure of the gel after one freeze-thaw cycle is stable and tight, and the swelling rate is the lowest.

[0054] Example 3 (1) Preparation of MCT emulsion: Weigh 6% MCT by mass, add 3% Tween 80 by mass as an emulsifier, high-speed shear for 5 min, and then use a high-pressure homogenizer to homogenize three times at a pressure of 70 MPa to obtain MCT emulsion.

[0055] (2) The steps for preparing the gel are as follows: ① Weigh 2.1% sodium alginate and stir it with a constant temperature magnetic stirrer for 2 h to obtain a sodium alginate solution with a certain mass fraction; ② Weigh 0.31% calcium carbonate powder and add it to the sodium alginate solution, ultrasonicate for 30 min, and continue stirring for 2 h with a constant temperature magnetic stirrer; ③ Weigh 0.7% chitosan powder and add it to the sodium alginate-calcium carbonate mixture, ultrasonicate for 60 min, and stir overnight; ④ Weigh a certain amount of gluconolactone (GDL) powder and add it to the mixed solution, stir it quickly and evenly, and then let it stand to form a hydrogel.

[0056] (3) Sample preparation steps: Sample 1: After step ①, add MCT, then proceed to step ②③④. Sample 2: After steps ①②③, add MCT, then proceed to step ④. Sample 3: After step ①, add MCT solution, then proceed to step ②③④. Sample 4: After steps ①②③, add MCT solution, then proceed to step ④.

[0057] Effect Example 3 1. Determination of MCT embedding rate (1) Surface oil content Accurately weigh 2 g of gel into a conical flask, add 25 mL of petroleum ether and shake for 5 min. Pour the mixed solution into a funnel, filter it, and wash it with 25 mL of petroleum ether. Collect the filtrate in a round-bottom flask that has been dried to constant mass, evaporate it to dryness on a rotary evaporator, and then place the round-bottom flask in a vacuum drying oven at 60°C to dry to constant mass. Weigh and calculate the surface oil content. (2) Total oil volume Refer to GB5009.168-2016 "National Food Safety Standard Determination of Fatty Acids in Food", and select the acid hydrolysis method. Accurately weigh 2 g of gel sample, add 10 mL of hydrochloric acid solution and mix well, place the flask in a 70℃ water bath for 40 min, and shake once every 10 min. After the hydrolysis of the flask is completed, cool it to room temperature. After cooling, add 10 mL of 95% ethanol and mix well, transfer to a separatory funnel, rinse the flask with a mixture of petroleum ether and ether, let the solution in the separatory funnel stand and stratify, and then rotary evaporate to dryness. The final amount of residue is the total amount of oil in the microcapsules.

[0058] Where: W0——total oil content of gel (g); W1——oil content on the surface of gel (g) 2. In vitro simulated release kinetics study Table 11 SGF and SIF solution preparation Simulated gastric digestion: Take 5 g of gel and add 5 mL of water. Use a high-speed shearing machine to homogenize at a shear rate of 4000 r / min. Take the homogenized sample solution and add 8 mL of SGF and 1 mL of pepsin (121.21 mg / mL). Adjust the pH to 2 with 1 mol / L HCl, and place it in a constant temperature water bath at 37°C and oscillate at 130 r / min for 1 h.

[0059] Simulated small intestinal digestion: Take 20 mL of digestive fluid after gastric digestion and adjust the pH to 7. Add 10 mL of SIF (2 mg / mL lipase, 20 mg / mL bile salt, 10 mmol / LCaCl2) preheated at 37°C for 5 min, and place the mixed solution in a constant temperature water bath at 37°C and oscillate at 130 r / min for 2 h. Use a pH meter to measure the pH of the reaction system, add a certain concentration of NaOH solution to maintain the pH value of the system at 7, record the volume of NaOH consumed, and calculate the release of free fatty acids during the digestion process. The formula is: Where: V t represents the volume of NaOH consumed / (L); c represents the concentration of NaOH solution / (0.1 mol / L); M represents the molar mass of MCT / (g / mol); and m represents the mass of MCT in 5 g of gel / (g).

[0060] 3. Data analysis and processing Origin 2021 software was used to draw charts and IBM SPSS Statistics 27 software was used for data analysis. Each sample was repeated at least three times, and the experimental data were expressed as mean ± standard deviation.

[0061] (1) Determination of embedding efficiency according to Fig.12 The results showed that the embedding rates of groups 3 and 4 were higher than those of groups 1 and 2, and the best embedding effect was in group 3, with an embedding rate of 94.62%. As can be seen from the figure, there is little difference in the embedding rates between groups 1 and 2, and there is no significant change in the embedding rates between groups 3 and 4, indicating that adding MCT before and after gelation has no significant effect on the embedding rate of the samples. The embedding rates of samples in groups 3 and 4 were relatively high, indicating that adding emulsified MCT can improve the embedding rate, which may be because the emulsified MCT can better fuse with the CS and SA solutions, and the emulsified MCT liquid particles are smaller, and the molecules are easier to diffuse, making them evenly distributed in the solution, thereby increasing their embedding rate.

[0062] (2) SEM structural analysis The hydrogel film was observed by SEM. Fig.13 ) shows that the upper and lower surfaces of the gel are porous structures. The interconnectivity of the pore structure and the integrity of the connection indicate that the hydrogel film has good structural stability, which can effectively improve the mechanical properties of the hydrogel and maintain the morphology after water absorption and swelling. Among them, compared with the blank gel, the sample image can show spherical oil droplets, indicating that MCT is embedded in the gel and the embedding effect is good. Finally, the emulsified MCT was selected as the addition to the gel.

[0063] (3) Fourier transform infrared spectroscopy The FTIR results show that Fig.14 It can be seen that for CS, 3200 cm -1 The nearby peak is formed by the overlap of the absorption peaks of OH bond and NH bond, 2900 cm -1 It is caused by the stretching vibration of the CH bond, 1652 cm -1 The absorption peak nearby is the amide I peak of acetylamino, at 1560 cm -1 There is a bending vibration of NH (amide II) at 1065 cm -1 is the CC skeleton stretching vibration absorption peak. In the FT-IR spectrum of SA, 1600 cm -1 and 1406 cm -1 The characteristic absorption peak of chitosan is at 1640 cm -1 and 1586 cm -1 The two characteristic peaks at 1378 cm-1 represent the stretching vibration of C=O and the bending vibration of NH in amide. -1 and 1066 cm -1 represent CN and COC stretching vibrations, 1100 cm -1 Represents the NH bending vibration of secondary amines. MCT at 2900 cm -1 There are characteristic peaks near 1700 cm, which are mainly caused by the stretching vibration of =CH bond; -1 The characteristic peak near 1000 cm is due to the stretching vibration of C=O bond. -1 The characteristic peak near 1000 cm is due to the stretching vibration of CO bond. -1 The following characteristic peaks are mainly due to CC bond vibration. As can be seen from the figure, the spectra of sample 1 and sample 2 are similar, indicating that adding MCT before and after gelation has no effect on the sample structure of the final gel formation; the characteristic peaks of the three substances CS, SA and MCT are included in the spectra of samples 1 and 2, which determines that the gel encapsulating MCT is formed, and no new peaks appear in the infrared spectrum of the final gel sample, indicating that in the gelation process, the combination of the three substances CS, SA and MCT does not involve changes in chemical bonds.

[0064] (4) In vitro digestion ① In vitro simulated digestion core material release rate The release rate of MCT and MCT gel in simulated intestinal fluid digestion in vitro Fig.15As shown in the figure, within 0 h~1.5 h, MCT and MCT gel enter the intestinal fluid for digestion, the reaction is relatively fast, and the release rate increases rapidly. Starting from 1.5 h, the release of MCT and MCT gel increases slowly, which may be because the longer the digestion time, the less MCT content in the sample, and the slower the release rate. Compared with the digestion rate of MCT, the release rate of gel-encapsulated MCT is significantly slower, so it means that the release of gel-encapsulated MCT is slow and stable during the simulated digestion process in vitro, and there is no sudden release phenomenon, achieving a sustained release effect. The fatty acid release rate of groups 1 and 2 is lower than that of groups 3 and 4, which may be due to the increase in the cross-linking density of the sodium alginate microgel emulsion, the unemulsified MCT, the aggregation of the emulsion droplets, and the reduction of the contact surface area between lipase and the emulsion droplets, which leads to a decrease in the emulsion digestion rate.

[0065] Cumulative release rate of frozen-thawed and unfrozen-thawed samples of embedded MCT gel Fig.16 As shown in the figure, within 0~3.0h, the release rate of the frozen-thawed and non-frozen-thawed gels first increased rapidly and then digested slowly. As can be seen from the figure, in the comparison between each group of frozen-thawed and non-frozen-thawed, the digestion rate of the frozen-thawed group is higher than that of the non-frozen-thawed group, and the digestion is faster. The reason is that the gel structure after freezing and thawing is destroyed, the pores in the gel become larger, and the contact area with the digestive fluid becomes larger, so the digestion rate of MCT increases. Compared with the rate curve of MCT emulsion digestion alone, the digestion rate of MCT hydrogel after embedding is slower, achieving the purpose of sustained release.

Claims

1. SA / CS / Ca 2+ The preparation method of double network hydrogel is characterized in that: The following steps are involved: (1) Weigh sodium alginate, add it into distilled water, and stir to obtain a sodium alginate solution; (2) Weigh a certain amount of calcium carbonate powder, add it to the sodium alginate solution, and continue stirring using a constant temperature magnetic stirrer after ultrasonic treatment to obtain a sodium alginate-calcium carbonate mixture; (3) Weigh a certain amount of chitosan powder, add it to the sodium alginate-calcium carbonate mixture, and stir overnight after ultrasonication; (4) Weigh a certain amount of gluconolactone (GDL) powder, add it to the mixed solution, quickly stir it evenly, and then let it stand to form a hydrogel; (5) The hydrogel is subjected to freeze-thaw treatment.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass concentration of the sodium alginate solution is 0.01-0.03 g / mL.

3. The preparation method according to claim 1 or 2, characterized in that: In step (2), the mass ratio of calcium carbonate to sodium alginate is 0.1-0.5:1-3; the ultrasonication time is 30 min; and the stirring time is 2 h.

4. The preparation method according to claim 1 or 3, characterized in that: In step (3), the mass ratio of the chitosan powder to sodium alginate is 1-3:1-3; and the ultrasonic time is 60 min.

5. The preparation method according to claim 1 or 4, characterized in that: In step (4), the mass ratio of gluconolactone to chitosan is 0.25:1-3.

6. The preparation method according to claim 1 or 5, characterized in that: In step (5), the freeze-thaw treatment is to place the hydrogel in a -80°C refrigerator for 24 h and then thaw it at 4°C for 24 h.

7. A SA / CS / Ca2+ double network hydrogel prepared by the preparation method according to any one of claims 1 to 7.

8. SA / CS / Ca as claimed in claim 7 2+ Application of double network hydrogel in preparing composite materials by embedding MCT.

Citation Information

Patent Citations

  • 3D printing method of sodium alginate / polyvinyl chloride all-physically-crosslinked double-network hydrogel scaffold

    CN106178106A

  • Method for preparation of core-shell structure microcapsule based on gel network limited anti-solvent technique

    CN109012520A

  • Alginate complex gel stent material constructed based on homogeneous phase crosslinking and layer-by-layer self-assembly technology and preparation method thereof

    CN110302427A

  • Antibacterial fresh-keeping composite freeze-thawed edible film for chilled fresh meat and preparation method thereof

    CN111925541A

  • Preparation method of glucolactone-induced corn starch-based hydrogel

    CN117624646A

Cited By

  • Preparation method of soil conditioner with double functions of water retention and adhesion

    CN120399149A

  • Composite hydrogel, preparation method and application

    CN121005921A

  • Shape-controllable and decrosslinkable homogeneous polyelectrolyte hydrogel as well as preparation method and application thereof

    CN121673590A